MORPHOLOGICAL VARIATION IN THE EBONY AND SILVER LEAF MONKEYS [TRACHYPITHECUS AURATUS (E. GEOFFROY, 1812) AND TRACHYPITHECUS CRlSTATUS (RAFFLES, 1821)] FROM SOUTHEAST ASIA - IBNU MARYANTO; I. MANSJOER; D. SAJUTHI; J. SUPRlATNA (Treubia, 1997)
The morphological variation in the ebony and silver leaf monkeys (Trachypithecus auratus and T. cristatus) from Southeast Asia; Thailand, Malaya, Bintan, Sumatra, Serasan-Natuna, Kalimantan and Java were studied using multivariate analysis approaches. The results showed that clinal variation in skull; dental and dentary morphology was found in Java. The skull; dental and dentary characters showed an increase from West to East with Central Java as an intermediate fonn. Consequently, in Java there should be only one subspecies, T. a. auratus. Meanwhile, there are four morpholgical groups of Trachipithecus cristatus, those are of Thailand, Malaya-Sumatra-Kalimantan, Bintan and Natuna. The Malayan population, presumably is the same as Bintan population while Sumatra-Kalimantan forms an intermediate.